Combined Use of Eucalyptus salmonophloia Essential Oils and the Parasitoid Dinarmus basalis for the Control of the Cowpea Seed Beetle Callosobruchus maculatus - Soumaya Haouel-Hamdi; Nada Abdelkader; Mariam Hedjal-Chebheb; Ezzeddine Saadaoui; Emna Boushih; Jouda Mediouni-Ben Jemâa (Tunisian Journal of Plant Protection, 2018)

(untitled)
This work aims to evaluate the possible combined use of Eucalyptus salmonophloia essential oils and the ectoparasitoid Dinarmus basalis for the control of the cowpea seed beetle Callosobruchus maculatus, a serious pest of economic importance on stored legumes including chickpea. This study carried out first investigation on the insecticidal potential of E. salmonophloia grown in Gabès (South Tunisia). Fumigant toxicity of the essential oils was tested against pest adults and larvae (L1, L2 and L3 larval stages). The parasitoid was introduced respectively 3 and 6 days after oil application against the fourth instar larvae and nymphs of the target pest. Results reported the interesting insecticidal potential of E. salmonophloia essential oils against C. maculatus L1, L2 and L3 larvae and adults. Oils significantly inhibited the parasitism potential of D. basalis. Indeed, at the concentration 12.5 µl/l air, the emergence rate of D. basalis adults decreased from 93.33% for the control to 40 and 28.33%, respectively, at 3 and 6 days following oil application. Storage of seeds using plant-based insecticides and essential oils is not always compatible with biological control strategies. Thus, identifying components that have lower effects on natural enemies is very important for a successful IPM program.